2021
DOI: 10.1002/hed.26776
|View full text |Cite
|
Sign up to set email alerts
|

Oncologic outcomes of transoral robotic surgery for HPV‐negative oropharyngeal carcinomas

Abstract: Background Patients with human papillomavirus (HPV)‐negative oropharyngeal squamous cell carcinoma (OPSCC) continue to experience disappointing outcomes following chemoradiotherapy (CRT) and appreciable morbidity following historical surgical approaches. We aimed to investigate the oncologic outcomes and perioperative morbidity of a transoral robotic surgery (TORS) approach to surgically resectable HPV‐negative OPSCC. Methods Retrospective analysis HPV‐negative OPSCC patients who underwent TORS, neck dissectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 59 publications
1
8
2
Order By: Relevance
“…Reports showed that HPVnegative OPSCCs located at the base of the tongue are more likely to have positive surgical margins in TORS. 14,37 However, in our 58 HPVnegative patients, tonsillar tumors stood a higher proportion, which might explain a low rate of positive margin in our data. Together, these suggest that TORS achieves satisfactory R0 resection in patients with T1-T2 stage OPSCC and postoperative complications are controllable.…”
Section: Follow-up and Survival Outcomescontrasting
confidence: 53%
“…Reports showed that HPVnegative OPSCCs located at the base of the tongue are more likely to have positive surgical margins in TORS. 14,37 However, in our 58 HPVnegative patients, tonsillar tumors stood a higher proportion, which might explain a low rate of positive margin in our data. Together, these suggest that TORS achieves satisfactory R0 resection in patients with T1-T2 stage OPSCC and postoperative complications are controllable.…”
Section: Follow-up and Survival Outcomescontrasting
confidence: 53%
“…Negative surgical margins were obtained in 80.4% of patients. Crude swallowing outcomes were favorable as well 23 . Only 5.4% of patients required a gastrostomy tube at 1 year, 23.2% received a gastrostomy tube perioperatively or during adjuvant therapy 23 .…”
Section: Discussionmentioning
confidence: 93%
“…23 Only 5.4% of patients required a gastrostomy tube at 1 year, 23.2% received a gastrostomy tube perioperatively or during adjuvant therapy. 23 These results come in contrast to earlier work in the pre-TORS era demonstrating comparable oncologic outcomes between surgically based treatment versus radiation therapy based treatment, with more severe or fatal complications occurring in surgically treated patients. 3,24 As a consequence, this established radiation therapy as the dominant treatment modality at most centers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations